Thiazole: A simple scaffold with tremendous therapeutic potential - Bharti S.K.; Mahapatra D.K.; Singh S.K. (My University, 2025)
The treatment of infectious diseases still remains an important and challenging problem. Despite the availability of novel antimicrobial agents, still there is growing interest in this field. Many compounds have been synthesized with this aim but their clinical use has been limited by relatively high toxicity, bacterial resistance and/or lack of desired pharmacokinetic properties. A major research emphasis to counter this growing problem is the development of antimicrobials structurally unrelated to the existing molecules. One possibility to achieve this goal is the combination of two antimicrobial agents as a single molecule with appropriate biological activities. © 2015 by Apple Academic Press, Inc.